2022
DOI: 10.3168/jds.2021-21150
|View full text |Cite
|
Sign up to set email alerts
|

Association of housing and management practices with milk yield, milk composition, and fatty acid profile, predicted using Fourier transform mid-infrared spectroscopy, in farms with automated milking systems

Abstract: Milk fatty acid (FA) profile can be divided into (1) de novo (C4-C14) that are synthesized in the mammary gland; (2) preformed (≥C18) that are absorbed from blood and originate from mobilized adipose tissues or dietary fat; and (3) mixed (C16), which have both origins. Our objectives were to describe the FA profile, as predicted using Fourier transform mid-infrared spectroscopy, of bulk tank milk from automated milking system (AMS) farms and to assess the association of management and housing factors with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Farms with lower de novo FA, on average, produced less milk fat and protein per cow per day (Woolpert et al 2016). Similar associations between housing and management practices and bulk tank FA composition were also observed by Castro et al (2022). Milk FA have also been identified as potential predictors for enteric methane emissions (Bougouin et al 2019).…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Farms with lower de novo FA, on average, produced less milk fat and protein per cow per day (Woolpert et al 2016). Similar associations between housing and management practices and bulk tank FA composition were also observed by Castro et al (2022). Milk FA have also been identified as potential predictors for enteric methane emissions (Bougouin et al 2019).…”
Section: Introductionmentioning
confidence: 68%
“…Similar associations between housing and management practices and bulk tank FA composition were also observed by Castro et al . (2022). Milk FA have also been identified as potential predictors for enteric methane emissions (Bougouin et al .…”
Section: Introductionmentioning
confidence: 99%
“…A recent Canadian survey [37] showed that ~60% of dairy producers either misconceived or were unaware of the actual changes in their milk yield and SCC. Moreover, recent Canadian studies [38,39] associated milk production and quality in AMSs with herd-level housing factors and management practices rather than the AMS alone. Therefore, it is reasonable to surmise that future studies more rigorously isolating the relative impact of AMS adoption on milk production and quality are needed for large dairy herds representing the USA demographics captured by the current survey.…”
Section: Discussionmentioning
confidence: 99%
“…As we conducted the trial on only one farm, the findings are representative of cows on a single diet with a farm-specific management style. As seen in Castro et al (2022) , management practices such as feed pushing style, feed delivery frequency, bedding type, raking frequency, and barn design all contribute to milk FA concentrations recorded in cows. Grummer (1991) noted that milk fat can be altered through the diet (e.g., feeding a low roughage diet to increase levels of C18:1), and milking frequency and ration energy levels also change milk composition ( Wagner-Storch and Palmer, 2003 ; Beerda et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%